Identification of reinforcement structures of composite constructions based on the results of harmonic oscillation tests - Yankovskii, Andrey Petrovich (Computational Continuum Mechanics, 2010)
The problem of identification of the reinforcement structures of thin-walled composite constructions is formulated based on the results of steady-state vibration experiments. A special case of shells of revolution with axisymmetric reinforcement structures is considered. Rehabilitation of the reinforcement structure of a cylindrical shell is performed under pseudo-realistic experimental conditions. It is shown that the accuracy of identification of the reinforcement structure and the effective elastic moduli of the composite construction is quite satisfactory.
Keywords: composites; reinforcement structure identification; inverse problems